Co-evolution, neo-cybernetic emergence and phenomenologies of ambiguity: Towards a framework for understanding interactive arts experiences. Issue 3 (1st December 2016) - Castellanos, Carlos
This article provides an overview of research into how certain forms of interactive art, what I call the 'emergent arts', facilitate or amplify a construction of a reality that is active, dynamic, collaborative and co-evolutionary with our increasingly technologized environment. By examining these artworks and experiences via the interlocking frames of cybernetics, phenomenology and posthumanist thought, this research articulates the movement towards a framework that fuses theoretical and experiential modes of enquiry to provide insights relevant to both interactive artists and humanities scholars. I will discuss two primary components of this framework. The first is a taxonomical model that outlines a number of characteristics of new media and interactive arts practice that engage in processes that establish a foundation for the shifts in perceptual and embodied experience that I characterize as 'symbiogenic'. The second major component is a sketching out of the conceptual basis of the symbiogenic framework, allowing us to go deeper into examining the dynamics of what I call co-evolution by outlining four theoretical concepts that I consider to be the cornerstone of what I call symbiogenic experiences in the emergent arts: ambiguity and unknowability, boundary, distributed intentionality and collectively emergent autonomy.